Search for Bs0 oscillations using inclusive lepton events - BARATE, R. (Institutional Knowledge at Singapore Management University, 1999)
A search for B0sBs0 oscillations is performed using a sample of semileptonic b-hadron decays collected by the ALEPH experiment during 1991–95. Compared to previous inclusive lepton analyses, the proper time resolution and b-flavour mistag rate are significantly improved. Additional sensitivity to B0sBs0 mixing is obtained by identifying subsamples of events having a B0sBs0 purity which is higher than the average for the whole data sample. Unbinned maximum likelihood amplitude fits are performed to derive a lower limit of Δms>9.5ps−1Δms>9.5ps−1 at the 95% confidence limit (95% CL). Combining with the ALEPH D−sDs−-based analyses yields Δms>9.6ps−1Δms>9.6ps−1 at 95% CL.